Impact of regionally increased CO2 concentrations in coupled climate simulations - Semmler, Tido; Pithan, Felix; Jung, Thomas (Zenodo, 2019)
In which direction is the influence larger: from the Arctic to the mid-latitudes or vice versa? To answer this question, CO2 concentrations have been regionally increased in different latitudinal belts, namely in the Arctic, in the northern mid-latitudes, everywhere outside of the Arctic and globally, in a series of 150 year coupled model experiments with the AWI Climate Model. This method is applied to allow a decomposition of the response to increasing CO2 concentrations in different regions. It turns out that CO2 increase applied in the Arctic only is very efficient in heating the Arctic and that the energy largely remains in the Arctic. In the first 30 years after switching on the CO2 forcing some robust atmospheric circulation changes, which are associated with the surface temperature anomalies including local cooling of up to 1°C in parts of North America, are simulated. The synoptic activity is decreased in the mid-latitudes. Further into the simulation, surface temperature and atmospheric circulation anomalies become less robust. When quadrupling the CO2 concentration south of 60°N, the March Arctic sea ice volume is reduced by about two thirds in the 150 years of simulation time. When quadrupling the CO2 concentration between 30 and 60°N, the March Arctic sea ice volume is reduced by around one third, the same amount as if quadrupling CO2 north of 60°N. Both atmospheric and oceanic northward energy transport across 60°N are enhanced by up to 0.1 PW and 0.03 PW, respectively, and winter synoptic activity is increased over the Greenland, Norwegian, Iceland (GIN) seas. To a lesser extent the same happens when the CO2 concentration between 30 and 60°N is only increased to 1.65 times the reference value in order to consider the different size of the forcing areas. The increased northward energy transport, leads to Arctic sea ice reduction, and consequently Arctic amplification is present without Arctic CO2 forcing in all seasons but summer, independent of where the forcing is applied south of 60°N. South of ...